Book Review: Geopolítica Ambiental: A construção ideológica do Desenvolvimento Sustentável (1945-1992) [Environmental Geopolitics: The Ideological Construction of Sustainable Development (1945-1992)], by Leandro Dias. - Claudio Luiz Zanotelli (Geografares, 2021)
This book is the result of a doctoral thesis defended, in 2011, at the Instituto de Geociências da Universidade Estadual de Campinas [Geosciences Institute of the State University of Campinas] – UNICAMP, which received an Honorable Mention from the Capes Prize [Menção Honrosa do Prêmio Capes] in 2012. The author reveals in this book the process of the United Nations Conference on the Environment and Development (UNCED) and the Forum of Non-Governmental Organizations and Social Movements – Global Forum, in 1992. Leandro Dias, thus contributes to revealing the intricacies of the Conference and the resulting Agenda, analyzing, among other things, the global geopolitics of sustainable development. This book it is an indispensable reading to understand how major events change the dynamics of social and socio-environmental processes.